UPAYA INOVASI KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN HARMONI KERAGAMAN AGAMA DAN BUDAYA DI STAIN KERINCI (SEBUAH INOVASI PENDIDIKAN KARAKTER) - Alam, Masnur (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2015)
The implementation of Islamic Education in Kerinci STAIN has not done kaffah (comprehensive), it was still partial, fanaticism, apologists, conservative, ritualistic. So to face the future, since the second semester of 2014 the course material of PAI and Philosophy of Islamic Education has been innovating the curriculum which was relevant to the needs of the times with themes that can respond to contemporary issues related to harmony in diversity, issues of peace, togetherness, compassion, gentleness, love each other. It also presenting the concept of an accommodative education, develop an attitude is not redundant (moderation). Be able to harmonize diversity (diversity) cultures and religions, can be away from prejudice (suusdzdzan) and put it in the context of prejudice (husunudzdzan). So that the existence of Islamic Education truly a blessing, great teaching, conditioning and adhesives for social life, not as a doctrine of extreme, radical, exclusive, discriminatory, as a trigger or provocator of conflicts, divisions and carrier culprit curse.Â Pelaksanaan Pendidikan Agama Islam di STAIN Kerinci selama ini belum dilakukan secara kaffah, masih bersifat parsial, fanatisme,apologis, konservatif, ritualistik. Maka dalam menghadapi masa depan, sejak semester genap 2014 mata kuliah Materi PAI dan Filsafat Pendidikan Islam telah melakukan inovasi kurikulum yang relevan dengan kebutuhan zaman dengan tema-tema yang dapat merespons isu-isu kontemporer yang berkaitan dengan harmoni dalam keragaman, masalah kedamaian, kebersamaan, kasih sayang, kelemah-lembutan, saling mencintai. Menghadirkan konsep pendidikan yang akomodatif, mengembangkan sikap tidak berlebih lebihan (moderation). mampu mengharmonisasi diversity (keragaman) budaya dan agama, dapat menjauhi prasangka buruk (suâusdzdzan) dan meletakkannya dalam konteks prasangka baik (husunudzdzan). Sehingga eksistensi Pendidikan Agama Islam betul-betul menjadi rahmat, ajaran yang agung, penyejuk dan perekat bagi kehidupan sosial, bukan sebagai ajaran yang ekstrim, radikal, eksklusif, diskriminatif, sebagai pemicu atau propokator konflik, biang kerok perpecahan dan pembawa laknat.